High-performance work system: differences between the perception of employees and the intention of human resources managers in SMEs in Colombia - Monsalve-Castro, Carolina; Pardo-del-Val, Manuela; Dasi-Rodríguez, Sonia; Luzardo Briceño, Marianela (Cuadernos de Administración, 2022)
The purpose of this paper is to establish whether there is a difference in the use of high-performance practices as conceived by human resources managers (as responsible for their implementation) and how these practices are perceived by employees. Starting with a description of the high-performance practices within the Human Resources Management, we proceed to review the most common classifications and conclude with the proposal of a measurement scale to be applied in the business sector of the city of Bucaramanga in Colombia, where 50 SMEs and 651 employees participate. For the validation of the instrument, a confirmatory factor analysis was carried out to demonstrate its good psychometric properties and the information was analyzed by means of descriptive statistics. The results show that there are differences in the perception of employees and the implementation of managers in some practices, such as retribution and training. Finally, we conclude with the need to continue making a distinction between the practices applied by management (intentional) and those that are experienced by the individuals of an organization (perceived), with the purpose of strengthening the human resources systems that lead to achieve the proposed objectives through positive attitudes on the part of the collaborators.